In vitro evaluation of palm fronds as feedstuff on ruminal digestibility and gas production (Acta Scientiarum. Animal Sciences, 2018)
This study was carried out to evaluate using palm fronds only or supplemented with fibrolytic enzymes as alternative roughage on the ruminal nutrients digestibility and gas production. Treatments were: clover hay (Trifolium alexandrinum), palm fronds only and palm fronds plus fibrolytic enzymes (enzymes were mixed with palm fronds in rate of 4 g kg-1 of dry matter (DM). The results showed a reduction (p < 0.05) in gas production, ammoniac nitrogen (NH3-N, DM and organic matter (OM) digestibility in palm fronds compared with clover hay. While supplementing palm fronds with fibrolytic enzymes improved DM and OM digestibility compared with palm fronds only without (p < 0.05) differences with clover hay. Also, supplementing palm fronds with fibrolytic enzymes reduced (p < 0.05) gas production compared with other treatments. It could be concluded that adding fibrolytic enzymes improved the utilization of palm fronds as alternative roughage without negative effect on nutrients digestibility and reduced gas production which improve the environmental aspects of feeding ruminant animals.